2021
DOI: 10.35251/gjaas.2021.001
|View full text |Cite
|
Sign up to set email alerts
|

Review of Poultry Production and Poultry Vaccine Manufacture in Nepal

Abstract: Poultry industry is one of the strong pillars of Nepal’s agricultural production system, contributing around 4% in the national gross domestic product (GDP). Nepal is self-reliant in poultry meat and egg production. This sector provides employment to thousands of people and has become a major source of income to rural people. Low investment cost, less manpower requirement, and quick returns attract many investors towards poultry farming and hence the population and productivity of poultry is increasing year af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Nepal is an agricultural country where the farming system is mostly subsistence-based, and crops and livestock farming are integrated. Livestock along with fisheries contribute around 12.5% of the total GDP, while the poultry sector alone contributes nearly 4% of total GDP [ 14 ]. The Nepal Commercial Poultry Survey, 2014–2015, showed that there are 7368 (35%) commercial poultry farms in Bagmati province and 2993 (14%) in Gandaki province [ 15 ], which are the areas of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Nepal is an agricultural country where the farming system is mostly subsistence-based, and crops and livestock farming are integrated. Livestock along with fisheries contribute around 12.5% of the total GDP, while the poultry sector alone contributes nearly 4% of total GDP [ 14 ]. The Nepal Commercial Poultry Survey, 2014–2015, showed that there are 7368 (35%) commercial poultry farms in Bagmati province and 2993 (14%) in Gandaki province [ 15 ], which are the areas of this study.…”
Section: Introductionmentioning
confidence: 99%
“…As per the latest livestock statistics, the standing population of fowl is around 83 million which is over 200% greater compared to the population 10 years ago [2]. In Nepal, poultry industry has over a billion-dollar investment, provides employment to over 150,000 people, and contributes around 4% to the national gross domestic product (GDP) and 8% to the national agricultural GDP (AGDP) [3]. Poultry farming, including the backyard poultry, is an important aspect of income generation in rural areas while chicken meat and eggs serve as the major source of protein in Nepalese kitchen [3].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination against ND is commonly practiced in the commercial farms while its use is limited in the backyard poultry of Nepal [10]. ND vaccination strategy is conventional and mostly utilizes the live-attenuated F, LaSota, I-2 or R2B strains administered through intraocular route, in drinking water, or in muscles [3,11]. First vaccination at 5-7 days is followed by periodic boosts in laying hens [11].…”
Section: Introductionmentioning
confidence: 99%
“…About 27.1% of total Gross Domestic Product (GDP) is contributed by Agriculture and Forestry. 19 Livestock and dairy sector contribute 32% of agricultural GDP and 11% of national GDP. 20,21 Cattle and buffaloes are considered to be major livestock reared in Nepal.…”
Section: Introductionmentioning
confidence: 99%